Nutri-Score: a public health tool to improve eating habits in Portugal - Goiana-da-Silva, Francisco (2019)
This article intends to help filling the existing gap in guidance for the implementation of FOP labelling systems.4 As such, the following sections present the growing evidence on the impact of the Nutri-Score labelling scheme in promoting healthier eating behaviours and informs health professionals, as well as decision makers, on the way forward.